Traditional Cultural Short Video Publicity System Based on Data Mining and Digital Image Technology - Xiaoyue Guo; Jingjing Feng (Advances in Multimedia)
With the continuous development of the social economy, more and more attention has been paid to traditional cultures, such as Chinese-style clothing, decoration, and furniture, and the publicity of traditional culture is also diverse. However, it should be noted that the rise of short videos has promoted the diversification of traditional culture publicity methods. In this paper, data mining technology and digital technology are introduced. By sorting out the content, publicity strategy, and emphasis of traditional culture, and through correlation analysis, the audience of traditional culture has been wider, and the content has been transmitted more, aiming to make more Chinese people love traditional culture and promote traditional culture. The simulation results show that data mining and digital technology are effective and can effectively promote the propaganda of short videos of traditional culture.